Analytics and big data for accountants - Lindell, Jim (John Wiley & Sons, Inc., 2017)
This book prepares accountants to: -Deal with major trends in predictive analytics, optimization, correlation of metrics, and big data.-Interpret and manage new trends in analytics techniques affecting your organization.-Use new tools for data analytics.-Critically interpret analytics reports and advise decision makers.